Optimization and decision-making in the renewable energy industry - Balo, Figen, 1972-; Topal, Ayse, 1983-; Demir, Ezgi, 1991-; Ulutas, Alptekin, 1983- (Advances in environmental engineering and green technologies (AEEGT) book series., 2022)
"The main objective of this book is to analyze renewable energy sources using current mathematical methods and techniques, giving an introduction of trends and current mathematical methods to the masses and providing advanced knowledge on renewable energy sources for both academic and practical professionals"--